Do DNA copy number changes differentiate uterine from non-uterine leiomyosarcomas and predict metastasis? - Svarvar, Catarina (2006)
DNA copy number changes were investigated in 51 (19 uterine and 32 nonuterine) primary leiomyosarcomas by comparative genomic hybridization. The aim was to evaluate whether true biological differences exist between uterine and nonuterine leiomyosarcoma and whether changes revealed by comparative genomic hybridization have prognostic value. Genomic imbalances were found in 48 (94%) cases. The most frequent DNA copy number changes were losses in 10q (35%), 13q (57%), and 16q (41%), gains in 1q (41%), and gains and high-level amplifications in 17p (39%). Gains were nearly as frequent as losses in both uterine and nonuterine leiomyosarcoma. Correlation-based tree modeling revealed two clusters that segregated significantly a group of uterine (gains at 1q11-q24) and a group of nonuterine (losses at 13q14-q34, 16q11.1-q24, and 10q21-q26) cases. The nonuterine cluster was associated with subcutaneous origin and a trend toward increased metastasis-free survival. Further explorative analyses identified aberrations associated with shorter metastasis-free survival time, including losses at 2q32.1-q37 and gains at 8q24.1-q24.3, whereas the cases with losses at 6cen-p25 showed longer metastasis-free survival time.